2017
DOI: 10.3390/ijms18061125
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin Attenuates Pulmonary Hypertension in Chronically Hypoxic Rats

Abstract: Chronic hypoxia induces pulmonary hypertension and vascular remodeling, which are clinically relevant to patients with chronic obstructive pulmonary disease (COPD) associated with a decreased level of nitric oxide (NO). Oxidative stress and inflammation play important roles in the pathophysiological processes in COPD. We examined the hypothesis that daily administration of melatonin (10 mg/kg) mitigates the pulmonary hypertension and vascular remodeling in chronically hypoxic rats. The right ventricular systol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
26
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(29 citation statements)
references
References 51 publications
2
26
0
1
Order By: Relevance
“…Por lo tanto, una disminución de la COX-2 podría ser indicador de menor estrés oxidativo e inflamación pulmonar. Con respecto a lo anterior, se ha demostrado que melatonina disminuye el estrés oxidativo y la presión pulmonar en neonatos 15,16 y adultos 26 de modelos animales. Los efectos antioxidantes de melatonina están asociados a sus características de: 1) scavenger de radicales libres, 2) inducción de la maquinaria enzimática antioxidante y 3) disminución de la expresión de enzimas prooxidantes 27 , lo cual disminuye el tono oxidativo en el territorio pulmonar 15,17,18 .…”
Section: Discussionunclassified
“…Por lo tanto, una disminución de la COX-2 podría ser indicador de menor estrés oxidativo e inflamación pulmonar. Con respecto a lo anterior, se ha demostrado que melatonina disminuye el estrés oxidativo y la presión pulmonar en neonatos 15,16 y adultos 26 de modelos animales. Los efectos antioxidantes de melatonina están asociados a sus características de: 1) scavenger de radicales libres, 2) inducción de la maquinaria enzimática antioxidante y 3) disminución de la expresión de enzimas prooxidantes 27 , lo cual disminuye el tono oxidativo en el territorio pulmonar 15,17,18 .…”
Section: Discussionunclassified
“…[41] A recent study reported that melatonin significantly attenuated the levels of RV systolic pressure, thickness of the arteriolar wall, oxidative and inflammatory markers in the hypoxic animals with a marked increase in the endothelial nitric oxide synthase phosphorylation in the lung. [42] Hung et al concluded their finding that that melatonin attenuated pulmonary hypertension by reversing injury caused due to the oxidative stress in lungs and restoring nitric oxide production. [42] Melatonin also have protective effects on cardiac tissues and thereby protects heart, due to antiatherosclerotic activities.…”
Section: Cardiovascular Systemmentioning
confidence: 99%
“…[42] Hung et al concluded their finding that that melatonin attenuated pulmonary hypertension by reversing injury caused due to the oxidative stress in lungs and restoring nitric oxide production. [42] Melatonin also have protective effects on cardiac tissues and thereby protects heart, due to antiatherosclerotic activities. [43,44] In 2015, Cheng et al, demonstrated that melatonin treatment had significantly reduced the number and areas of atheromatous plaques in an animal model involving rabbit.…”
Section: Cardiovascular Systemmentioning
confidence: 99%
“…Useful results might derive by other approaches. Recently, it has been reported that the administration of antioxidants and anti-remodeling agents associated with the vasodilator therapies could have beneficial effects in new-borns [40][41][42][43][44][45][46] . From this point of view, melatonin (N-acetyl-5-methoxytryptamine, an indoleamine molecule), appears to be an effective agent for PHN, markedly improving pulmonary vascular function.…”
Section: Melatonin and Metforminmentioning
confidence: 99%
“…However, the date until now obtained derive only from animal studies. Consequently, future studies should be performed for: (1) optimizing doses and/or therapeutic windows to improve the functional and anti-remodeling effects in animal models, as preclinical studies ; and (2) extending these investigations to human pregnant women and new-borns [40][41][42][43][44][45][46] .…”
Section: Melatonin and Metforminmentioning
confidence: 99%